Influence of social networks on women’s contraceptive decision-making and action: a qualitative study in two districts in Uganda - Catherine Birabwa; Dinah Amongin; Peter Waiswa; Beth Phillips; Ronald Wasswa; Lauren Suchman; Erica Sedlander; Kelsey Holt; Lynn Atuyambe (BMC Public Health)
Abstract Background Women in sub-Saharan Africa often lack agency to make their own contraceptive decisions, more so in rural settings. Evidence indicates that social networks influence contraceptive decision-making and behaviours but there is limited information on the dynamics between women and their network members. We explored ways in which women’s social networks influenced their agency to make contraceptive decisions. Methods We conducted an exploratory qualitative study, between February and May 2021, among 60 women (15–45 years) from two largely rural districts in Uganda. Data were collected using semi-structured audio-recorded in-depth interviews which were transcribed verbatim. We used thematic analysis guided by constructs from social network mechanisms to analyze the data. Results Half of the participants were adolescents (15–19 years) and 62% (37/60) were current contraception users. We found that participants most commonly involved partners, relatives, and peers in their contraceptive decision-making. Social support emerged as the most common mechanism through which these network members influenced women’s agency in making and acting on their contraceptive decisions. This was mainly in the form of informational and emotional support. Informational support, mostly provided by relatives and peers, included advice to adopt contraception particularly given to participants who desired to better manage their families, describing lived experiences, directing women to formal contraceptive services, and sharing perceived/actual side effects of contraceptive use. Emotional support, provided by partners and relatives, involved acknowledging and validating decisions, as well as providing reassurance regarding contraceptive experiences. Some women also received instrumental support (reminders to get dose/method and exempting women from responsibilities to go seek contraceptive services). The mechanism of social influence was also at play with social pressure to give birth. Conclusions Our study highlights how different types of social support from partners, relatives, and peers can either bolster or undermine women’s agency in making contraceptive decisions. Informational support from relatives and peers can boost women’s certainty in their intentions, while emotional support from partners boosts their confidence to act on these intentions. Multipronged approaches targeting these networks are necessary to promote women’s agency in making contraceptive decisions.